The Implementation of Case Study through Field Observation Tasks to Enhance Students' Understanding of the Role of Mosques - Muhammad Hilmy (Universitas Negeri Yogyakarta, 2026)
This study aimed to improve students’ understanding of the roles and functions of mosques through the implementation of case-based learning combined with field observation tasks in the Islamic Religious Education course at Politeknik Negeri Banyuwangi. The study employed Classroom Action Research using two cycles, namely planning, action, observation, and reflection. The participants were 23 students. Data were collected through learning achievement tests, observation, documentation, and field observation assignment sheets, and were analyzed using quantitative and qualitative techniques. The findings showed that students’ initial understanding of the roles and functions of mosques was still limited and tended to be theoretical. The mean pre-test score was 67.7. After the implementation of case-based learning through field observation tasks, the mean score increased to 77.2 in Cycle I and 83.3 in Cycle II. The learning process also became more active, contextual, and reflective, as students were able to connect conceptual knowledge with socio-religious realities in the community. These findings indicate that case-based learning through field observation tasks was effective in enhancing students’ cognitive understanding, analytical ability, and learning engagement. Therefore, this instructional model is relevant for vocational higher education contexts that require the integration of theory and field experience.